Probiotic Supplement Enhances the Hematological Parameters and Immune Response of Common Carp against Fish Pathogen Aeromonas hydrophila - Nisha , M. Barakath; Muralidharan, M.; Priyadharshini , J.; Mohideen, R. Ajaz Haja (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Probiotic bacteria play an important role in the growth and health of aquatic animals by improving their immune system. A 60-day experiment study was carried out to evaluate the effect of probiotic bacteria Bacillus subtilis dietary supplement enhances the hematological parameters and Immune response of fish Common carp against the pathogenic Aeromonas hydrophila. The experimental fish with an average mean weight of 15.15 ± 1.05 g were distributed randomly into 3 groups (Control (CTRL (Basal feed and without A. hydrophila), Exp1 (Basal feed and with A. hydrophila, and Exp2 (108 CFU/ml with probiotic supplement with A. hydrophila). On the 56th day, experimental groups were then challenged with A. hydrophila (1.0 × 107 CFU/mL), after 72 hrs of infection, blood samples were collected randomly from five fish from each group. Results showed that probiotic supplementation improved Hematological parameters such as RBCs, WBCs, Hb, PCV, and Immune response parameters (Nitroblue Tetrazolium Activity, aminotransferase, Serum lysozyme activity, total protein, and immunoglobulin). This present study suggests that the probiotic diet enhances the disease resistance against Aeromonas hydrophila in the culture of Common carp.